EDUCATION ON PLASTIC WASTE MANAGEMENT WITH THE 3R (REDUCE, REUSE, AND RECYCLE) - Taufik Huda Taufik Huda; Andhika Lungguh Perceka Andhika Lungguh Perceka; N. Ai Erlinawati N. Ai Erlinawati; Herlin Rusyani Herlin Rusyani; Aceng Ali Awaludin Aceng Ali Awaludin (LP4M STIKes Karsa Husada Garut, 2025)
The issue of plastic waste has become an urgent environmental problem in Indonesia, including on the campus of STIKes Karsa Husada Garut. Plastic waste, which is difficult to decompose, can pollute the environment and pose health risks. To address this problem, a waste management education program based on the 3R principle (Reduce, Reuse, Recycle) was implemented with the aim of increasing knowledge, shaping environmentally friendly behavior, and encouraging creative waste management practices. The implementation method includes preparation, education through interactive lectures and workshops, field practice with the creation of separate waste bins, the making of ecobricks, and creative products from plastic waste, as well as monitoring and evaluation of the program's success. The results of the activities show an increase in participants' knowledge of 35-40%, behavioral changes such as reduced use of plastic bags and disposable bottles, and the development of creative products from plastic waste. Program evaluation confirms the effectiveness of participatory methods and hands-on practices in building awareness and internalizing sustainability values. This program also has implications for the formation of an environmentally friendly culture on campus, which can serve as a model for other educational institutions. Thus, 3R-based education not only reduces the negative impact of plastic waste but also fosters environmentally conscious students who are able to apply sustainability principles in their daily lives.